Root K Affinity Drivers and Photosynthetic Characteristics in Response to Low Potassium Stress in K High-Efficiency Vegetable Soybean - Liu, Changkai; Wang, Xue; Tu, Bingjie; Li, Yansheng; Chen, Heng; Zhang, Qiuying; Liu, Xiaobing (Frontiers in Plant Science, 2021)
Significant variations of potassium absorption and utilization exist in vegetable soybean. Pot and hydroponic experiments were carried out to examine the characteristics of root potassium (K) affinity-associated drivers and photosynthesis in vegetable soybean (edamame) [Glycine max (L.) Merr.] with different K efficiency. Two K high-efficiency vegetable soybean genotypes (Line 19 and Line 20) and two K low-efficiency genotypes (Line 7 and Line 36) were investigated in low K and normal K conditions. The root of K high-efficiency genotypes had a higher K+ affinity associated with a higher maximum K+ uptake rate (Imax), but lower Michaelis constant for K+ absorption (Km) and lower compensation concentration for K+ uptake (Cmin). Seedlings of K high-efficiency genotypes also had higher root vigor [triphenyl tetrazolium chloride (TTC) reduction method] and greater absorbing activity (methylene blue method), especially in the low K condition. Furthermore, the root bleeding-sap rate of K high-efficiency genotypes in low K stress was 9.9–24.3% greater than that of normal K conditions, which was accompanied by a relatively higher K concentration of root bleeding-sap in contributing to K+ upward flux. The root of K high-efficiency vegetable soybean genotypes exhibited K+ high-affinity and driving advantages. Photosynthetic parameters of K high-efficiency vegetable soybean genotypes were less affected by low K stress. Low K stress decreased the net photosynthetic rate of K high-efficiency genotypes by 6.1–6.9%, while that of K low-efficiency genotypes decreased by 10.9–15.7%. The higher chlorophyll (Chl) a/b ratio with enhanced relative content of Chl a in response to low K stress might be an adapted mechanism for K high-efficiency genotypes to maintain photosynthetic capacity. Stronger root K affinity drivers associated with photosynthetic adaptability to low K stress are the key factors in determining the K high-efficiency of vegetable soybeans.